The Emergence of Nepali Dalit Literature - Hutt, Michael (Far Western Review, 2023)
The under-representation of Dalits in Nepali-language literature until the late 20th century— both as the subjects of texts and the authors of texts—is very striking, and a category of Nepali-language writing labelled dalit sahitya only began to emerge after 1990. This paper report draws upon research on this issue conducted in 2021-22. First, it introduces a selection of Nepali-language texts produced by non-Dalits in which Dalit characters and Dalit-related issues have been portrayed. Most of these were published before Dalits began to author such texts themselves; a few are of more recent origin. It then offers a preliminary thematic summary of the Dalit-authored literature that has appeared in more recent years, and a summary of the debate that has arisen about the definition of dalit sahitya and the authoritative representation of Dalit issues in Nepali-language literature.